Analisis Praktik Tarah Pada Jual Beli Buah Jeruk Pada Petani Kecamatan Bangorejo Kabupaten Banyuwangi Perspektif Mazdhab Syafi’i - Yunus Zamroji; Ribut Suprapto; Babun Suharto (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study aims to analyze the practice of tarah in the sale and purchase of citrus fruit by farmers in Bangorejo District, Banyuwangi Regency, from the perspective of the Shafi'i School of Law. The approach used in this study is qualitative, with data collection techniques through observation, interviews and documentation. The results of the analysis say that tarah or pieces of weight taken by the buyer, is a form of gift from the seller whose law is sunnah, because the tarah taken by the buyer is written in the note and there is willingness from the seller, in addition, giving tarah from the seller is a form of practice to make it easier to carry out buying and selling transactions, where Allah SWT promises to give mercy to sellers who make it easier for buyers.